The determination of physical activity, nutrition and self-sufficiency levels of sedanter individuals of fitness club member - N. Demirci; Demirci P. Toptaş (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Purpose : This study was planned to determine the physical activity (PA), nutrition and self-efficacy levels of sedentary individuals have long been members of fitness clubs Material : A total of 80 participants were divided into two groııps according to body mass index (BMI) according to their obesity status: Group 1 (overvveight obesity (OW)) and Group 2 (Normal Weight (NW)). All participants were watched for a year. The stııdy includes questionnaires on PA, eating habits, nutrition knovvledge and self-efficacy. Descriptive statistics including frequency, percentiles, ınean and Standard deviation were used. The T test was used to examine differences between PA, eating habits, nutrition knowledge and self-efficacy. Statistical significance was accepted as P <0.05. Results : Regarding participants' eating habits, the OW group was less frequent breakfast (P <0.05) and snack (P <0.01), ate more meals (P <0.01). When coınpared with the NW group, they showed less desirable behavior during the meal (P <0.05 for men). OW men spent less time (P <0.01) during vveekdays or weekends while doing less PA (P <0.01). OW woınen sat more in the vveekdays or weekends (P <0.01) and spent less time walking or riding a bicycle (P <0.05) than the NW group. The nutritional information of the OW and NW groups was not significantly different. Especially PA self-efficacy in OW was significantly lower than in NW group (P <0.01). Conclusion : This study revealed differences betvveen PA, eating habits and self-efficacy betvveen OW and NW individuals. Sedanter individuals who are members of fitness clubs should exercise exercise programs to prevent obesity and to increase the confidence about exercise or physical activity.